Characterisation of Neutropenia-Associated Neutrophil Elastase Mutations in a Murine Differentiation Model In Vitro and In Vivo. - Michael Wiesmeier (PLoS ONE, 2016)
Severe congenital neutropenia (SCN) is characterised by a differentiation block in the bone marrow and low neutrophil numbers in the peripheral blood, which correlates with increased risk of bacterial infections. Several underlying gene defects have been identified in SCN patients. Mutations in the neutrophil elastase (ELANE) gene are frequently found in SCN and cyclic neutropenia. Both mislocalization and misfolding of mutant neutrophil elastase protein resulting in ER stress and subsequent induction of the unfolded protein response (UPR) have been proposed to be responsible for neutrophil survival and maturation defects. However, the detailed molecular mechanisms still remain unclear, in part due to the lack of appropriate in vitro and in vivo models. Here we used a system of neutrophil differentiation from immortalised progenitor lines by conditional expression of Hoxb8, permitting the generation of mature near-primary neutrophils in vitro and in vivo. NE-deficient Hoxb8 progenitors were reconstituted with murine and human forms of typical NE mutants representative of SCN and cyclic neutropenia, and differentiation of the cells was analysed in vitro and in vivo. ER stress induction by NE mutations could be recapitulated during neutrophil differentiation in all NE mutant-reconstituted Hoxb8 cells. Despite ER stress induction, no change in survival, maturation or function of differentiating cells expressing either murine or human NE mutants was observed. Further analysis of in vivo differentiation of Hoxb8 cells in a murine model of adoptive transfer did not reveal any defects in survival or differentiation in the mouse. Although the Hoxb8 system has been found to be useful for dissection of defects in neutrophil development, our findings indicate that the use of murine systems for analysis of NE-mutation-associated pathogenesis is complicated by differences between humans and mice in the physiology of granulopoiesis, which may go beyond possible differences in expression and activity of neutrophil elastase itself.